Chemical Reactions on MHD Couple Stress Fluids towards Stretchable Inclined Cylinder - Suman Sharma; Shalini Jain (Journal of Heat and Mass Transfer Research)
This study focuses on exploring the influence of homogeneous and heterogeneous chemical reactions on a couple of stress fluids surrounding a permeable inclined stretching cylinder. The impact of a uniform magnetic field and porous media is also considered in the fluid model. It is assumed that the diffusion coefficients for chemical species A and B are of similar magnitudes and that the heat released during the chemical reaction is negligible. The governing partial differential equations (PDEs) are evolved and transformed into ordinary differential equations (ODEs) using adequate similarity alterations. These ODEs are subsequently solved using the shooting technique in conjunction with the fourth-order Runge-Kutta method, implemented through MATLAB software. Results are presented through graphs and tables depicting the velocity, temperature, and concentration fields. Furthermore, numerical findings for the skin friction coefficient and Nusselt number are discussed. The concentration field experiences a decline as homogeneous-heterogeneous reactions intensify, attributable to the heightened dispersion of concentrations across the system, resulting in a more intricate distribution pattern.